Research Impact Evaluation Tools: Myths and Reality - Rawat, Bhupesh; Bist, Ankur Singh; Maulani, Giandari; Azizah, Nur; Oganda, Fitra Putri (Pandawan Sejahtera Indonesia, 2022)
Research is one of the core activities for enhancing existing human capabilities. Research papers, patents, copyright, trademark etc. are used to represent novel ideas and experimental findings. Our aim is to discuss various tools that are used to measure the research impact of researchers among communities. This paper also discusses several critical issues which have emerged due to the malpractice in the academic and research community.